The application of adjectives, as well as issues and solutions around their usage (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
This article is about the superlative adjectives, monosyllabic superlative adjectives, polysyllabic superlative adjectives, stem-changing adjectives. this article also discusses the words used with superlative adjectives and by far.